Role of family in supporting children with mental disorders in Qatar - Abdulnaser A. Fakhrou; Taha R. Adawi; Sara A. Ghareeb; Atef M. Elsherbiny; Maryam M. AlFalasi (Heliyon, 2023)
Background: Mental disorders can significantly impact children's lives and affect their emotional, cognitive, and behavioral development. Family support and care is critical to the well-being of children, particularly children with mental disorders. However, given the “gap” between research and practice“,” there have been very few studies in the Arab region that focus on the role of the family in supporting children with mental disorders. The study also examines how families cope with caring for a person with mental disorders and what behaviors may influence the patient's distress. In addition, the study will examine the importance of family rehabilitation and integration of people with mental disorders into society. Methods: The study adopts the descriptive-analytical method and uses a questionnaire to gather data from the participants. The 350-parents sample (with 113 boys, 237 girls) was selected from the Shafallah Center for Integrating People with Disability. Morgan's law is used to determine the sample size. Results: The results show that there are statistically significant differences in the role of family members in supporting people with mental disorders due to two variables: Gender and Work. Age has no statistically significant effect on the role of family members in supporting people with mental disorders. Conclusion: This study is the first study conducted to investigate the role of family in supporting children with mental disorders in the Gulf Cooperation Council (GCC) in general and Qatar in particular. The results show that families should cope with the needs of a person with a mental disorder. Family rehabilitation is important in the care of people with mental disorders. There are certain behaviors of family members that can increase or decrease stress for the person. The results suggest that the family plays an essential role in supporting and promoting the lives of people with mental disorders and recommending effective ways to cope with them.